2003
DOI: 10.1034/j.1600-0587.2003.03449.x
|View full text |Cite
|
Sign up to set email alerts
|

The saproxylic beetleBolitophagus reticulatus: its frequency in managed forests, attraction to volatiles and flight period

Abstract: T. 2003. The saproxylic beetle Bolitophagus reticulatus: its frequency in managed forests, attraction to volatiles and flight period. -Ecography 26: 421-428.Reduction in amount of dead trees in Scandinavian forests due to intensive forest management has aroused interest in the requirements of saproxylic (wood-living) species. Much attention has been focused on Bolitophagus reticulatus, a tenebrionid beetle that lives on polypore fruiting bodies of Fomes fomentarius. Although earlier studies have suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 31 publications
0
27
0
1
Order By: Relevance
“…That the movement of adults of Bolitophagus cornutus (Panzer) across super-patches (logs) is restricted was confirmed by a mark-and-recapture study (Heatwole & Heatwole, 1968). The frequent shortdistance movements and infrequent long-distance dispersal of adults of B. reticulatus (L.) occur in only a few weeks in summer (Jonsell et al, 2003).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…That the movement of adults of Bolitophagus cornutus (Panzer) across super-patches (logs) is restricted was confirmed by a mark-and-recapture study (Heatwole & Heatwole, 1968). The frequent shortdistance movements and infrequent long-distance dispersal of adults of B. reticulatus (L.) occur in only a few weeks in summer (Jonsell et al, 2003).…”
Section: Introductionmentioning
confidence: 81%
“…Toda et al, 1999;Wertheim et al, 2000). Empirical studies have demonstrated that restricted movements occur at much larger scales than a patch, but at a smaller scale than limitation by dispersal (Heatwole & Heatwole, 1968;Rukke & Midtgaard, 1998;Jonsell et al, 2003). Although the combined effect of patch-and super-patch-level aggregation did not increase stability, certain super-patches attracted more individuals and consequently more species of insects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because for O. eremita, the occupancy per tree was systematically lower in smaller stands (and thus, the species was absent in many of the smallest stands), which not would be the case if the beetles readily moved between trees belonging to different stands. For B. reticulatus this was not analysed by Rukke and Midtgaard (1999), however, in a study by Jonsell et al (2003) found only a very small genetic differentiation at a larger geographical scale, between their two study areas. They found significant genetic differentiation between trees, probably due to a founder effect .…”
mentioning
confidence: 92%
“…Compared to other methods, such as population genetic analyses, telemetry, and dispersal simulators (i.e. flight-mills), the MRRbased results tend to give lowest dispersal estimates due to underestimation of long-distance movements (Koenig et al, 1996;Jonsell et al, 2003;Drag et al, 2011;Chiari et al, 2013;David et al, 2013;Oleksa et al, 2013), and vary due to local conditions and/or sampling designs (e.g. Stevens et al, 2010;Hassal & Thompson, 2012).…”
Section: Introductionmentioning
confidence: 99%